Singularity as a (di)solution of the subject-object problem: A reading from Spinoza and Deleuze. - Campillos Morón, Luis Ángel (Analysis. Journal of Philosophical Research, 2024)
Abstract: In this this paper we will reflect on the concept of singularity in Deleuze (according to his reading on Spinoza). We will present singularity as a way of dissolving the inveterate subject-object problem that runs through the history of philosophy. We will look for the attributes of singularity and its relations with the Spinozian concept of conatus. Here a political reading will be imbricated, according to the meanings of the forces that Deleuze takes from Nietzsche: the (active) singularities persevere in their potency, while the (reactive) entities generate impotence and Power. Later, we will insert necessity, freedom and will in this conceptual frame, we will stop at the critique of anthropocentrism. We will conclude associating the problem of measurement in science with our study and anchoring various current ecological-political proposals in this Spinozian-Deleuzian ontological framework.Keywords: singularity; Spinoza; Deleuze; subject; object.